Dom Emanuel Gomes de Oliveira e a educação superior em Goiás (1923 - 1955) - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This dissertation aims to analyze the contribution of the Catholic Church to the implantation of higher education in Goiás, during the episcopate of Dom Emanuel Gomes de Oliveira. He led a strong educational movement at all levels that was consolidated in several regions of the State, including laying the foundations for the future of establishing the first University of the Midwest. We will see that this project by Dom Emanuel was not isolated, but was immersed in a broader perspective, which involved the entire Brazilian episcopate, with the desire to establish a Catholic restoration in the country in the face of the secular movement of the State and the advancing society. In this perspective, we take as a central research problem the following question: how did Catholic higher education constitute itself as a fundamental part for the self-affirmation of the Catholic Church in Goiás and combat secularization in the episcopate of Dom Emanuel Gomes de Oliveira between 1923 to 1955? Starting from this question, we will address the first challenges that the referred bishop faced at the beginning of his bishopric and what were his initiatives to answer each of the questions presented. We will debate that the secularization process contributed to the advance of Protestantism in Goiás, and this caused the Catholic Church to react using education as one of the ways to contain this advance. In this same perspective, we will analyze how the Santa Casa de Misericórdia in Goiânia was founded, where the first three courses of Catholic initiative were hosted in the new capital, namely: Nursing, Pharmacy and Dentistry. In addition, we will analyze how the solidified base of Dom Emanuel took place, on which the Catholic University of Goiás, founded after his death, was built. To this end, we will present the 1948 Eucharistic Congress of Goiânia as the most important event that marked the convergence of forces for the foundation of the University of Central Brazil, which did not leave the paper, but which enabled the Catholic Church to continue its investments in higher education, mainly with the creation of the Faculty of Philosophy, Sciences and Letters, which later became the germ of the Catholic University. In addition, we will point out the participation of Dom Emanuel in the civil society initiatives that took place at this time for the foundation of new higher education courses, his participation was of fundamental importance for the consolidation of these courses, some of them added the base that resulted in the foundation of the Catholic University . For the development of this research, we analyzed an important set of documents that belonged to the official and personal archives of Dom Emanuel Gomes de Oliveira, as well as letters, minutes, reports, curricula, economic balance sheets that enabled us to collect important information contained in this dissertation. The path of instruction-education was the path chosen by the Catholic Church in Goiás as the most effective way of fighting secularism and maintaining its hegemony.
Dom Emanuel Gomes de Oliveira and higher education in Goiás (1923 - 1955)
Keywords: Igreja Católica; Educação superior; Laicização; Estado; Goiás; Dom Emanuel Gomes de Oliveira; Catholic Church; Higher education; State; Laicization; Goiás; Dom Emanuel Gomes de Oliveira; CIENCIAS HUMANAS::HISTORIA